Confused after spirometry: a unifying diagnosis - Williamson, John Charles (BMJ Case Rep, 2016)
A 67-year-old woman was diagnosed with transient global amnesia having presented with an abrupt and temporary disruption in her memory function. Her symptom onset came shortly after a visit to her general practitioner where she had performed bedside spirometry. Following symptom resolution, she was discharged home with reassurance.